Analisa Peningkatan Kualitas Layanan Pelanggan untuk Mengoptimalkan Kepuasan Pelanggan pada Industri Ratu D’laundry - Arlita Yunia Saputri; Syifa Yulianti; Nurlelah Nurlelah; Budiharjo Budiharjo (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
This study aims to evaluate improvements in customer service quality with the goal of increasing customer satisfaction at Ratu D'Laundry. The approach used is quantitative with a descriptive methodology, where data is collected through a survey that measures five main aspects, namely service quality, process speed, price and promotions, customer service, and overall satisfaction and loyalty levels. The results of this study indicate that most customers are satisfied with the services provided, especially in terms of laundry cleanliness, clothing fragrance, and the friendly attitude of staff in providing services. These results show that these factors play an important role in shaping customers' positive perceptions of service quality. However, this study also found several complaints related to service completion time, which is considered to still need improvement. Overall, this study confirms previous findings that service quality has a significant impact on customer satisfaction. The proposed strategy to improve service completion time is a key step in building trust, meeting consumer expectations, and encouraging long-term customer loyalty.